Systematics, distributions and bionomics of the Catopocerini (eyeless soil fungivore beetles) of North America (Coleoptera: Leiodidae: Catopocerinae) - Peck, Stewart B.; Cook, Joyce (Zootaxa, 2011)
This paper is a review and revision of the tribe Catopocerini (Coleoptera: Leoididae: Catopocerinae) of North America. It covers the following genera: Catopocerus Motschulsky, 1870 with five species east of the Mississippi River and the resurrected genus Pinodytes Horn, 1880 with 42 species in North America west of the Mississippi River. All species in the tribe are eyeless and wingless inhabitants of forest soil and litter. Larvae and adults probably feed on subterranean fungi. Pinodytes Horn is resurrected to valid generic status. A neotype is assigned for Catopocerus politus Motschulsky. Lectotypes are designated for Catops cryptophagoides (Mannerheim, 1852) (which is transferred to Pinodytes), and Pinodytes pusio Horn, 1892. The following new synonym is recognized: Catopocerus ulkei Brown, 1933 = Catopocerus politus Motschulsky, 1870. The 33 new species and their distributions are as follows: Pinodytes angulatus (NW Oregon, USA), P. borealis (central Alaska, USA), P. chandleri (N California, USA), P. colorado (Colorado, USA), P. constrictus (S California, USA), P. contortus (E California, USA), P. delnorte (NW California, USA), P. eldorado (E California, USA), P. fresno (central California, USA), P. garibaldi (NW Oregon, USA), P. gibbosus (S California, USA), P. haidagwaii (Haida Gwaii (formerly Queen Charlotte) Islands, British Columbia, Canada), P. humboldtensis (NW California, USA), P. idaho (NW Idaho, USA), P. isabella (N Idaho, USA), P. klamathensis (SW Oregon and NW California, USA), P. losangeles (S California, USA), P. marinensis (W California, USA), P. minutus (central California, USA), P. monterey ( SW California, USA), P. newtoni (Ozarks region to E Texas, USA), P. orca (SW Oregon, USA), P. parvus (NW California, USA), P. punctatus (W Idaho and E Washington, USA), P. sanjacinto (S California, USA), P. sequoia ( S central California, USA), P. setosus ( SW Oregon and NW California, USA), P. shasta (N California, USA), P. shoshone (N Idaho, USA), P. sinuatus (SW Oregon, USA), P. spinus (N central California, USA), P. tehama (N California, USA), and P. tuolumne (E central California, USA). The following new combinations are established: Pinodytes capizzii (Hatch, 1957), ex Catopocerus; P. cryptophagoides (Mannerheim, 1852), ex Catopocerus; P. imbricatus (Hatch, 1957), ex Catopocerus; P. newelli (Hatch, 1957), ex Catopocerus; P. ovatus (Hatch, 1957), ex Catopocerus; P. pusio Horn, 1892, ex Catopocerus; P. rothi (Hatch, 1957), ex Catopocerus; P. subterraneus (Hatch, 1935), ex Catopocerus; P. tibialis (Hatch, 1957), ex Catopocerus.